Dermatologic adverse events associated with targeted therapies for melanoma. Issue 3 (4th March 2022) - Scarpato, Luigi; Festino, Lucia; Vanella, Vito; Madonna, Gabriele; Mastroianni, Massimo; Palla, Marco; Ascierto, Paolo Antonio
ABSTRACT: Introduction: The development of new targeted therapies has considerably changed the therapeutic paradigm of melanoma, significantly increasing overall survival (OS) and progression-free survival (PFS). However, skin-related adverse sequelae might occur and impact on patients' quality of life. Areas covered: In this article we will cover the most important dermatological toxicities related to BRAF and MEK-inhibitors, along with updated management strategies. Expert opinion: BRAF inhibitors have represented a revolution in the treatment of melanoma. They have improved the outcome of the disease and therefore represent an important option in the management and care of patients with advanced melanoma. Skin toxicity (especially the onset of squamous skin carcinomas) has been considered a major cutaneous side effect and, although the addition of MEK inhibitors in combination has significantly reduced the incidence of skin sequelae, serious skin adverse events might develop anyway and impact significantly on patients'quality of life and on national health system budget. The introduction of BRAF and MEK inhibitors as a new effective adjuvant treatment option for stage III and ulcerated melanoma has proved a significant impact on the risk of recurrence, and may have interesting developments in the near future as a further therapeutic tool.